OPTIMIZATION OF THE DIALOGICAL PATROL OF THE SAMAPTA UNIT IN PREVENTING THE CRIME OF MOTOR VEHICLE THEFT IN THE JURISDICTION OF THE PEMALANG POLICE DISTRICT - CHRISTIAN ARJUNA MATANI (Advances in Police Science Research Journal, 2022)
, implementing, monitoring, while external factors such as the impact of the covid pandemic. performance of dialogical patrols at the Pemalang are the patrol targets that are still not right, the competence of the members is still lacking, discipline and anev and also the impact of Covid which the leadership focus This research is motivated by the non-optimal performance of dialogical patrols in overcoming the crime of theft at the Pemalang Station which is quite high so that the need for optimal performance from the Satsamapta to reduce theft cases with optimal performance. In this study, the author uses the concepts of optimization and dialogic and uses POAC management theory and communication. The techniques used are interviews, observations and document studies, then the method used is the. The discussion here is the optimization of the dialogical patrol performance which is still not optimal because there are still high theft cases and factors are internal and external factors. Internal factors such as planning, organizingdivided so that the implementation of patrols is less than optimal. The conditions expected by the Pemalang Police Satsamapta are that in carrying out dialogical patrols they can determine fixed targets, the ability of personnel in communication to be good, disciplined and in carrying out patrols there must be APP and Anev carried out by the leadership and the need for good cooperation between functions. So, to realize this expected condition, it is by implementing a mentor system or senior noncommissioned officer who has been taught to teach material to young non-commissioned officers so that their competence develops.